Features of early pregnancy treatment in women with luteal phase defect - A F Mikhelson; E Yu Lebedenko; T E Feoktistova; M P Kurochka; N B Kuznetsova; S M Nastueva (IP Berlin A.V., 2013)
The purpose of this study was the first pregnancy trimester flow analysis in patients with IDLF receiving pre-gravidity training including dydrogesterone taking. Materials and methods. The drug was prescribed to 60 patients at the pregnancy planning stage. After becoming pregnant patients were divided into two clinical groups: I - with dydrogesterone prolongation taking in trimester one (n = 36), II - dydrogesterone cessation after pregnancy verification (n = 24). The results overview. Significant differences in the incidence of adverse prenatal outcomes, with a predominance of those in clinical group II were obtained. Conclusion. Dydrogesterone discontinuation for up to 8 weeks of pregnancy, when used at the stage of preparation is irrational, as manifested not only as a threat, but the termination of pregnancy in the I trimester.